Physical dimension of masjid - towards children friendly masjid - Abu Bakar, Aniza; Zulkifely, Zur Atiqa; Abdul Majid, Noor Hanita; Ibrahim, Mohd Burhan (Abdullatif Al Fozan Award for Mosque Architecture, and Institut Terjemahan & Buku Malaysia Berhad, 2019)
Three design guidelines can be referred to in Malaysia when it comes to Masjid design. However, the guidelines seem to outline the main spaces according to the fundamental functions of masjids which is the congregational prayer, and talks. The guidelines also did not specify on children and their space requirements in the masjid. The size of the spaces as proposed by the Jabatan Perancangan Bandar dan Desa (JPBD) is 1m2/person. This study aims to identify the physical dimension of nine case studies masjids in the urban area of Kuala Lumpur and Selangor. The approach is rather quantitative in nature, and adopting the site inventory and analysis, and observation techniques. The result indicates exciting findings whereby it can be said that when it comes to the maximum carrying capacity of masjids, the human anthropometric/human scale is considered rather than the proposal by the JPBD.